2018
DOI: 10.3390/ani8030037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative Euthanasia Methods of Neonatal Chickens

Abstract: Simple SummaryMale layer chicks do not have economic value and are humanely killed after hatching. The layer industry is seeking alternative methods to humanely kill recently hatched male chicks. This study evaluated the use of gases or negative air pressure as a means of humane and viable alternatives to maceration. The treatments included carbon dioxide, nitrogen, reduced air pressure, and a negative control. The study showed that chicks exposed to treatments, gases or negative air pressure, did not differ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…More recently, exposure of chicks to LAP has been evaluated and reported to be a suitable method (Gurung et al., 2018b). In this study, preliminary trials showed that a negative air pressure of 15.3 kPa (1 kPa = 7.5 Torr) would result in 100% mortality and, therefore, the experimental chicks were subjected to a reduction in chamber pressure from 100.12 kPa to 15.3 kPa over 80 s and then held in the chamber for 5 min, resulting in death.…”
Section: Assessmentmentioning
confidence: 99%
“…More recently, exposure of chicks to LAP has been evaluated and reported to be a suitable method (Gurung et al., 2018b). In this study, preliminary trials showed that a negative air pressure of 15.3 kPa (1 kPa = 7.5 Torr) would result in 100% mortality and, therefore, the experimental chicks were subjected to a reduction in chamber pressure from 100.12 kPa to 15.3 kPa over 80 s and then held in the chamber for 5 min, resulting in death.…”
Section: Assessmentmentioning
confidence: 99%
“…(2018) found euthanasia with CO 2 resulted in the shortest time to insensibility and death. The authors also reported bird stress, as measured by serum corticosterone and serotonin levels, was similar for all the 3 methods ( Gurung et al., 2018 ).…”
Section: Introductionmentioning
confidence: 84%
“…Despite having National Farm Animal Care Council and AVMA approval, many hatcheries are looking for an alternative method of euthanasia to maceration owing to public concern. Recently, researchers have investigated a number of alternative methods for neonatal chicken euthanasia, including CO 2 gaseous euthanasia ( Gurung et al., 2018 ; Baker et al., 2019 ). Gaseous euthanasia is used for culling adult and neonatal poultry, during which exposure to high or prolonged concentrations of an inhalant agent, in this case CO 2 , results in insensibility and death ( Galvin et al., 2005 ; Raj et al., 2006 ; AVMA, 2013 ; Baker et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations